2008
DOI: 10.1088/0954-3899/35/7/075101
|View full text |Cite
|
Sign up to set email alerts
|

On the accuracy of multipole expansion of deformed density distribution

Abstract: The interaction potential for a deformed-spherical pair of nuclei is calculated using the folding model derived from different range nucleon-nucleon (NN) interactions. Five spherical projectiles of different mass numbers scattered on the 238 U deformed target are considered. The error in the heavy ion (HI) potential by using the truncated multipole density expansion is evaluated for each case. We find systematic trends of the percentage error in the HI potential depending on the number of multipoles considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
(63 reference statements)
1
16
0
Order By: Relevance
“…A similar study had been made in Ref. 17 for different ranges of the NN force. In this study the authors assumed the existence of quadruple and hexadecapole deformations and they found 17 that the accuracy of the three terms expansion increases with increasing both the range of NN force and the mass number of the incident projectile.…”
Section: The Accuracy Of Multipole Expansion In Calculating Hi-potentsupporting
confidence: 52%
See 3 more Smart Citations
“…A similar study had been made in Ref. 17 for different ranges of the NN force. In this study the authors assumed the existence of quadruple and hexadecapole deformations and they found 17 that the accuracy of the three terms expansion increases with increasing both the range of NN force and the mass number of the incident projectile.…”
Section: The Accuracy Of Multipole Expansion In Calculating Hi-potentsupporting
confidence: 52%
“…According to Table 1, the maximum error in the six terms is 11% for 40 Ca and 7% for 208 Pb which is still large. In fact when we use finite range NN force like Michigan 3-range Yukawa (M3Y)-interacting [15][16][17] (consists of two finite range terms and a zero range one) to calculate the Coulomb barrier parameters for spherical-deformed interacting pair, we expect that the error in the barrier parameters due to the six terms will be more smaller than the above values. This is because the barrier is combination of the finite range Coulomb interaction and the nuclear part which is derived from finite range and zero range terms.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To simplify the complications coming from the finite range of the proton-proton Coulomb force, the density multipole expansion of the deformed daughter has been used to calculate the Coulomb direct part [27,28]. If the ground states spin-parity of parent ( ) and daughter ( ) are not identical, we have then unfavored decay mode.…”
Section: Theoretical Formalismmentioning
confidence: 99%